1989
DOI: 10.1016/0304-3959(89)90210-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of fentanyl in lumbar and cervical CSF following lumbar epidural and intravenous administration

Abstract: Fentanyl (1 microgram/kg body weight) was administered intravenously and via a lumbar epidural catheter (in random order) on 2 separate occasions to 6 patients with chronic pain associated with non-terminal disease states. Frequent blood samples were collected from an indwelling intravenous catheter and CSF samples were collected via spinal needles inserted in the cervical (C7-T1 interspace) and lumbar (L3.4 interspace) regions at 0, 5, 10, 20, 30 and 45 min after fentanyl administration. The concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1
7

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(49 citation statements)
references
References 10 publications
1
40
1
7
Order By: Relevance
“…21,22 Rapid cephalad spread rather than systemic absorption with redistribution to the brain possibly causes the pruritus and hypotension seen with solutions of lipophilic opioids and plain local anesthetics. 6,7,[23][24][25][26] Both our study and that of Paez et al 27 support this explanation by showing less pruritus when fentanyl is combined with hyperbaric rather than plain bupivacaine. Although hypotension was not statistically different between both groups in our study, a trend towards hypotension requiring treatment was detected in parturients receiving the plain solution.…”
Section: Discussionsupporting
confidence: 87%
“…21,22 Rapid cephalad spread rather than systemic absorption with redistribution to the brain possibly causes the pruritus and hypotension seen with solutions of lipophilic opioids and plain local anesthetics. 6,7,[23][24][25][26] Both our study and that of Paez et al 27 support this explanation by showing less pruritus when fentanyl is combined with hyperbaric rather than plain bupivacaine. Although hypotension was not statistically different between both groups in our study, a trend towards hypotension requiring treatment was detected in parturients receiving the plain solution.…”
Section: Discussionsupporting
confidence: 87%
“…16 Lipid soluble opioids such as fentanyl also penetrate the dura following lumbar epidural administration and, as such, may reach cerebrospinal fluid (CSF) concentrations similar to those after intrathecal injection. 17 The slower onset of action of fentanyl given by the epidural rather than the intrathecal route may be because it must penetrate the dura to reach its site of action. Even though the CSE group initially obtained greater degree of analgesia, satisfaction was equal and excellent in both sets of mothers from shortly after the initial injection to the end of the study.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern characterized by a prompt onset of symptoms followed by a rapid decrease in intensity has been demonstrated in pharrnacokinetic studies of intravenous fentanyl in other patient populations. 25,26 It is essential that blinded observers not only note the presence or absence of symptoms, but that their interpretation of these symptoms facilitate appropriate clinical decisions. We have demonstrated that anaesthestists at various levels of training were able to interpret subjective symptoms and to determine correctly the route of fentanyl administration accurately 92.4% of the time.…”
Section: Discussionmentioning
confidence: 99%